Manusia yang Dijadikan Komoditas: Fenomena Human Trafficking di Provinsi Nusa Tengggara Timur - Goma Edwardus Iwantri (Populasi, 2020)
The phenomenon of human trafficking that makes humans as a commodity of trade is something that very alarming. In recent years since 2014 to 2018 the number of human trafficking cases in East Nusa Tenggara province has increased more than in other regions in Indonesia. In 2017, East Nusa Tenggara Province was ranked first of all Provinces in Indonesia related to human trafficking cases, where from January to August there were 137 cases of human trafficking in East Nusa Tenggara Province. This fact is certainly very alarming for all the people and the East Nusa Tenggara government. This article aimed at finding out 1) reality of the human trafficking case in East Nusa Tenggara Province, 2) human trafficking factors in East Nusa Tenggara Province, and 3) a solution to overcome human trafficking in East Nusa Tenggara Province. This article used literature study method by utilizing secondary data from various relevant sources. Human trafficking in East Nusa Tenggara Province have increased from year to year, it was reported that during the period of 2015 to mid-2016 there were 1,667 female migrant workers of human trafficking victims in East Nusa Tenggara Province. Low human resources as a result of low level of education and economic problems such us poverty and high unemployment are that main causes of human trafficking in East Nusa Tenggara Province. To overcame this, it is necessary to have concrete solutions like preventive action, empowerment, and improvement of the labor system.